Dynamic simulation of a compact sorption-enhanced water-gas shift reactor - Stadler, Tabea J.; Bender, Laila J.; Pfeifer, Peter (Frontiers in Chemical Engineering, 2022)
This work presents the dynamic simulation of a novel sorption-enhanced water-gas shift reactor used for synthesis gas production from pure CO in an e-fuels synthesis process. Due to the intended decentralized plant installation associated with fluctuating feed, process intensification and a compact reactor system is required. An optimized operating procedure was obtained by simulation-driven process design to maximize the sorbent loading and operate the process as efficient as possible. The process simulation is based on a simplified heterogeneous packed bed reactor model. The model accounts for simultaneous WGS reaction on a Cu-based catalyst and CO2 adsorption on a K-impregnated hydrotalcite-derived mixed oxide as well as subsequent desorption. An empirical rate expression was chosen to describe the water-gas shift reaction according to experimental data at 250 °C. Breakthrough experiments were performed and used to adapt kinetic adsorption (pressure: 8 bar) and desorption (pressure: 1 bar) parameters. The experimental CO2 sorption equilibrium isotherm was fitted with the Freundlich model. The reactor model was extended to a complex hybrid system scale model for the pilot plant reactor consisting of six individually accessible reaction chambers. Cyclic operation with automatized switching time adjustment was accomplished by a finite state machine. A case study exploited the benefits of a serial process configuration of reaction chambers. It could be shown that the sorbent loading can be remarkably increased through optimized operating strategies depending on the process conditions. Hence, the development of the hybrid model marks a crucial step towards the planned pilot plant operation and control.